(untitled) (Brazilian Journal of Radiation Sciences (BJRS), 2021)
The scattered radiation from interventional procedures is an important source of radiological risk for the medical staff. Considering all affected organs, the eye lens are among the most critical organs. As pointed out by several studies, even for low radiation doses, the appearance of cataract may occur. Considering this scenario, the radiation doses to the eye lens were determined using three different lead eyewear models commonly employed. The fluoroscopist was represented by an adult virtual anthropomorphic phantom (MASH3), coupled to the Monte Carlo code MCNP6.1™, in a typical cardiac interventional radiology procedure. The eyewear had thickness 0.5 mmPb each, and the evaluation was carried out for four different beam angulations (PA, LAO90, LAO65 e RAO65), 80 kVp of tube voltage and HVL of 4 mmAl. The results pointed out that the shielding efficiency has a strong dependence on the eyewear type utilized, which may be very useful for the decision-making during the acquisition of such equipments.